KONTAMINASI BAKTERI STAPHYLOCOCCUS SP PADA KEJADIAN LUAR BIASA KERACUNAN MAKANAN DI DUSUN SAWANGAN KABUPATEN MAGELANG JAWA TENGAH INDONESIA - Riska Epina Hayu (STIKes Al-Insyirah Pekanbaru, 2018)
Abstract On may 11, 2012, the Magelang District Health Departement was informed of a cluster of 25 patient with gastrointestinal illness after prayer session in the home of a resident. Since a food poisoning outbreak was suspected, an FETP team was sent to conduct an investigation to identify the source and recommend prevention and control measures. We did case-control study. There werw 25 cases and 16 controls. Cases were guasts who developed gastrointestinal signs and symptoms after the event. Control werw well attendees. Subjects were interviewed to obtain information on foods consumed. We also asked cases about onset of their illness, sign and symptoms experienced. Left-over food items were sent to laboratory for testing. There were 41 guests during the event of which 25 became ill (attact rate: 11.2%). The epidemic curve was that of a common source outbreak. Signs and symptoms of cases were diarrhea (76%), nausea (76%), abdominal pain (56%), weakness (48%), fever (40%), and vomiting (36%). Incubation periods ranged from four to nine hours (median: 6 hours). Cases were more likely than controls to have eaten chicken curry (OR 24, 95% CI; 2,4-1107.4) and chilli souce (OR 11.5, 95% CI: 1.67-124.22). Staphylococcal bacteria were found in the chicken curry. This food poisoning outbreak was probably caused by contaminated chicken curry. To prevent future outbreak, we recommended food handling practices, serve foods while hot (immediately after cooking or store in refrigerator and re-heat) and use clean cooking utensils.